An endemic species flock of Candonidae Kaufmann, 1900 (Crustacea, Ostracoda) from wells in Benin (Africa), with the description of a new subfamily, a new genus and five new species - Hotèkpo, Sourou Joseph; Schön, Isa; Martens, Koen (Zootaxa, 2024)
Between 2015 and 2022, over 200 wells were sampled in four catchment areas of Benin, using both Cvetkov plankton nets (funnel 200 µm mesh size, 150 µm below valve) and baited traps. As artificial wells serve as ecotones (interfaces between surface and groundwater ecosystems), the ostracod fauna is mostly represented by two families; Cyprididae (mainly epigeic) and Candonidae (hypogeic). Here, we describe a new subfamily of Candonidae from the wells in Benin, the Benincandoninae subfam. nov. Hotèkpo & Martens, represented by one genus, Benincandona gen. nov. Hotèkpo & Martens. We found 35 species belonging to this evolutionary radiation, of which we describe five new species: Benincandona martini gen. et spec. nov. Hotèkpo & Martens, B. ibikounlei gen. et spec. nov. Hotèkpo & Martens, B. sakitii gen. et spec. nov. Hotèkpo & Martens, B. cebios gen. et spec. nov. Hotèkpo & Martens and B. trapezoides gen. et spec. nov. Hotèkpo & Martens. The new subfamily and genus are characterised by a unique combination of characters, such as a seven-segmented antennula and a caudal ramus with a fully developed ramus, a single apical (anterior) claw and three short setae. Species within the genus can be distinguished by their carapace and hemipenis morphology, together with some limb characteristics. Whereas extensive subterranean candonid radiations have previously been reported from Europe, North and Central America and Northwest Australia (Pilbara), this is the first time such a vast radiation of subterranean candonids is reported from (West) Africa.